Arc behaviour on different materials in ASDEX Upgrade. (December 2021) - Rohde, V.; Balden, M.; Neu, R.
Highlights: The erosion of plasma facing components in a tokamak environment was systematically studied using different materials. The key parameter for the erosion is melting temperature of the material. For magnetic steel much stronger erosion is found compared to stainless steel. Abstract: Arcs, a source of dust particles and a localized erosion mechanism of the plasma-facing components, are found in all major fusion plasma devices. Measurements of arcs require diagnostics with high temporal and local resolution, which are not available at arc dominated locations in ASDEX Upgrade (AUG). To understand the erosion by arcing and to allow extrapolation for future fusion devices different materials are used to scan the material properties. In AUG, inserts were installed at the inner baffle region to measure the erosion by arcing. The use of polished inserts allows an accurate determination of the arc traces by depth maps obtained by laser profilometery. It turned out that the melting temperature of the materials is the main parameter for erosion. For tungsten mounted at the inner baffle, a region which is deposition dominated, an erosion rate by arcing of 1.2·10 13 at cm −2 s −1 is measured. For Beryllium, 9.5·10 13 at cm −2 s −1 is extrapolated from its thermal properties. As martensitic–ferritic low-activation steel is under discussion for the use in DEMO, magnetic steels were also investigated. Comparing stainless steel with magnetic steel, much deeper and wider craters are found in the latter one: they reach a depth of −80 μm. The erosion of magnetic steel by arcs is 40 times higher compared to stainless steel, which has almost the same physical properties.